ANALISIS KESALAHAAN SISWA DALAM MENYELESAIKAN PERMASALAHAAN OPERASI BENTUK ALJABAR DI MTsN 3 AGAM - Doni Ardia Putra; M. Imamuddin; Herlina Kumalasari (Universitas Pahlawan Tuanku Tambusai, 2022)
Algebra not only discusses problems related to number arithmetic operations, but also has a very broad scope, which makes it important to learn about. Because the scope of algebra is very wide, students also have some errors, therefore this research is aimed to describe the errors that occur and make tentative assumptions about why students make these mistakes. Researchers used descriptive qualitative research methods. Based on the result, researchers found several errors that occurred among these errors, namely the difficulty of operating using the distributive law, kabataku (kali (multiply) bagi (divide) tambah (add) kurang (minus)) to the distributive law, error when moving variables according to similar terms, all algebraic solutions are only one variable, errors 2 arithmetic operation signs, Algebraic fraction operation errors, and Missing variable errors when performing algebraic fraction operations. Kata kunci: error, student, algebra